From skyscrapers to sky savers: how New York City’s Local Law 97 advances climate resilience and public health - Chervonski, Ethan; Guerrero, Marisa A.; Rom, William N. (Frontiers in Climate, 2025)
Anthropogenic climate change, while once regarded primarily as an environmental concern, has evolved into a global health crisis. As a victim of escalating climate-related phenomena, New York City (NYC) has positioned itself at the forefront of climate resilience and public health action. Local Law 97 (LL97) is the latest in NYC’s long trajectory of climate action initiatives, setting progressively stringent caps on greenhouse gas (GHG) emissions from large buildings greater than 25,000 square feet. LL97 represents one of the most ambitious—and divisive—climate action policies in the United States and if successful, is poised to make NYC carbon neutral by 2050. At the same time, the potential public health benefits of LL97 are broad, including improved local air quality, decreased cost barriers to residential cooling, and if in principle applied to city buildings worldwide, reduced global GHG emissions capable of stabilizing global warming for posterity. Nevertheless, LL97’s reliance on a carbon-intensive electricity grid, creation of complex financial incentives, and divisive reception by political groups threaten its impact. The following paper reviews the public health consequences of building emissions through the lens of NYC’s built environment. It explores the role of LL97 and other relevant local and state legislation in mitigating the public health impacts of building emissions. Finally, the law’s limitations are critically assessed. By analyzing LL97’s potential successes and obstacles, this paper aims to provide actionable insights for other cities seeking to design effective climate action plans that balance sustainability, public health, and equity.